Mapa de recursos sociales para estudiantes universitarios - Martinez Lopez, Jose Angel; Miñano Sanchez, Sonia; Torralba Planes, Raquel; Marin, Longinos (EDITUM. Ediciones de la Universidad de Murcia, 2025)
The social resources map for university students is a guide of devices of any kind (benefits/services/programs/equipment) promoted by the Social Attention Office of the University of Murcia.From the administration of a questionnaire about the profile and living conditions of university students in 2021 at the University of Murcia, the areas of social need priority in university students were determined, serving as guidance for subsequent actions to be carried out. With the idea of ​​making social resources accessible to which university students are entitled by virtue of their need, public and private social entities were contacted, developing a joint work.The result of this collaborative work is this resource map that allows to offer updated information on: addictions, disability, mental illness, gypsy ethnicity, immigrants, LGTBI+, woman, poverty, refugees, eating disorders and housing.